2021
DOI: 10.3389/fpubh.2021.739003
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Healthcare Professionals and General Population Toward Vaccines and the Intention to Be Vaccinated Against COVID-19 in Spain

Abstract: Background: To achieve herd immunity, the acceptance of the COVID-19 vaccine by the population, especially healthcare professionals, plays a key role. The objective of the present paper is to address the differences in attitudes among Spanish healthcare professionals compared with the general population regarding COVID-19 vaccination.Methods: This cross-sectional study included data from 2,136 adults (n = 664 healthcare professionals) from an online survey conducted from May 6 to June 9, 2021. The Vaccination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
2
19
3
Order By: Relevance
“…Overall, no significant gender difference was observed between HCWs and the general population. However, based on results of Iguacel et al, (2021), females showed a statistically significantly higher percentage of mistrust compared to males [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, no significant gender difference was observed between HCWs and the general population. However, based on results of Iguacel et al, (2021), females showed a statistically significantly higher percentage of mistrust compared to males [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our previous study found increased odds of delaying vaccination for women [38], suggesting once more the changes associated with hesitancy over time. However, several studies reported lower odds of hesitancy for women [21], although this result was not always replicated [3,6,10,13,18,20,24,26,28]. When considering the month of response, the lower hesitancy for participants answering the questionnaire in September (versus November responders) lost statistical significance during the sensitivity analysis.…”
Section: Discussionmentioning
confidence: 89%
“…Hence, the reported vaccine acceptance or hesitancy was mostly assessed using hypothetical questions as there were still no vaccines available outside of the clinical trial setting [3][4][5][6][8][9][10]. Several cross-sectional studies have since explored COVID-19 vaccine acceptance and hesitancy and their determinants after the respective countries' vaccination program implementation, namely in European countries [2], such as the United Kingdom [15,16,20,21], Germany [15,22], Denmark [15,23], France [15], Hungary [15], Sweden [15], Italy [15], Norway [21], Poland [24], the Netherlands [25], Spain [26] and Greece [27]. Additional studies were also conducted in Saudi Arabia [28], the United States of America [13,17,21,29], South Africa [21,30], Jordan [31], Israel [32], Chile [33], China [18,21,34,35], Japan [21,36] and Australia [21], among others [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studying vaccine hesitancy in health professionals is important not only to understand what drives their hesitancy but also because they can highly influence the attitudes and behaviours of their patients towards vaccination. 18 …”
Section: Introductionmentioning
confidence: 99%